APPLICATION OF SAINTIFIC-INNOVATIVE LEARNING MODELS IN INDONESIAN TEACHERS - Astrawan, I Kadek Vera; Martha, I Nengah; Artika, I Wayan (Universitas Pendidikan Ganesha, 2019)
This study aims to examine the application of innovative-learning model that includes aspects of planning, implementation, evaluation, and constraints faced by Indonesian teachers in SMA Negeri 1 Kubu. The design of this research is descriptive-qualitative. The subjects of this research are 3 teachers and the object of this research is planning, implementation, evaluation, and obstacles of application of learning model. This research used observation, interview and documentation method. Data were analyzed using identification, classification, interpretation, presentation, and conclusion drawing. The results showed that (1) learning model planning is divided into two, namely syllabus and preparation of RPP. The syllabus used is derived from Kemdikbud and RPP is based on Permendikbud No. 103 year 2014. (2) implementation of learning based on scientific approach, ie observing, asking, trying, associating, and communicating. In addition, teachers vary the learning model with bamboo dancing, articulation, and active debate. (3) evaluation of learning based on curriculum 2013, that is assessment of process and result. (4) obstacles encountered include aspects of planning, implementation, and evaluation. The conclusion of this research is planning of learning model based on syllabus and RPP. Implementation of learning model based on scientific approach steps. Evaluation of learning model based on curriculum 2013, that is assessment of process and result. Constraints faced include aspects of planning, implementation, and evaluation. Teachers are advised to be more careful in preparing RPP and the school provides training related to the implementation of innovative-scientific model of learning.